Microscopic Image Analysis for Plant Tissue Using Image Processing Technique (International Journal of Engineering and Computer Science, 2017)
In this paper we analyze some microscopic images of plant tissue (xylem) using image processing technique. We capture the image with the help of Compound Laboratory Microscope. A compound laboratory microscope (CLM) is an advanced piece of lab equipment that utilizes light to create magnified images of specimens that are then projected onto an imaging mechanism. The deformation of plant tissue obtained at the scale of the two principal failure mechanisms: Cell breakage & cell separation. Different fundamental algorithm of image processing is implemented like edge linking and boundary detection of plant cells, image enhancement ,segmentation ,noise removal, morphological operation. A segmentation based problem to count number of white & black nano particles approximately in microscopic image